Network Pharmacology Prediction and Molecular Docking-Based Strategy to Discover the Potential Pharmacological Mechanism of Huai Hua San Against Ulcerative Colitis - Liu J; Liu J; Tong X; Peng W; Wei S; Sun T; Wang Y; Zhang B; Li W (Dove Medical Press, 2021)
Jiaqin Liu,1,2 Jian Liu,1,2 Xiaoliang Tong,3 Weijun Peng,4 Shanshan Wei,1,2 Taoli Sun,5 Yikun Wang,1,2 Bikui Zhang,1,2 Wenqun Li1,2 1Department of Pharmacy, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People's Republic of China; 2Institute of Clinical Pharmacy, Central South University, Changsha, Hunan, 410011, People's Republic of China; 3Department of Dermatology, The Third Xiangya Hospital, Central South University, Changsha, Hunan, 410013, People's Republic of China; 4Department of Integrated Traditional Chinese & Western Medicine, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People's Republic of China; 5School of Pharmacy, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People's Republic of ChinaCorrespondence: Wenqun LiDepartment of Pharmacy, The Second Xiangya Hospital, Central South University, No. 139 Renmin Road, Changsha, 410011, People's Republic of ChinaTel +86-731-85292093Email liwq1204@csu.edu.cnBackground: Huai Hua San (HHS), a famous Traditional Chinese Medicine (TCM) formula, has been widely applied in treating ulcerative colitis (UC). However, the interaction of bioactives from HHS with the targets involved in UC has not been elucidated yet.Aim: A network pharmacology-based approach combined with molecular docking and in vitro validation was performed to determine the bioactives, key targets, and potential pharmacological mechanism of HHS against UC.Materials and Methods: Bioactives and potential targets of HHS, as well as UC-related targets, were retrieved from public databases. Crucial bioactive ingredients, potential targets, and signaling pathways were acquired through bioinformatics analysis, including protein-protein interaction (PPI), as well as the Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Subsequently, molecular docking was carried out to predict the combination of active compounds with core targets. Lastly, in vitro experiments were conducted to further verify the findings.Results: A total of 28 bioactive ingredients of HHS and 421 HHS-UC-related targets were screened. Bioinformatics analysis revealed that quercetin, luteolin, and nobiletin may be potential candidate agents. JUN, TP53, and ESR1 could become potential therapeutic targets. PI3K-AKT signaling pathway might play an important role in HHS against UC. Moreover, molecular docking suggested that quercetin, luteolin, and nobiletin combined well with JUN, TP53, and ESR1, respectively. Cell experiments showed that the most important ingredient of HHS, quercetin, could inhibit the levels of inflammatory factors and phosphorylated c-Jun, as well as PI3K-Akt signaling pathway in LPS-induced RAW264.7 cells, which further confirmed the prediction by network pharmacology strategy and molecular docking.Conclusion: Our results comprehensively illustrated the bioactives, potential targets, and molecular mechanism of HHS against UC. It also provided a promising strategy to uncover the scientific basis and therapeutic mechanism of TCM formulae in treating diseases.Keywords: Huai Hua San, ulcerative colitis, network pharmacology, quercetin, JUN, PI3K/AKT signal pathway